PENGEMBANGAN WISATA PERKOTAAN BERBASIS PARTISIPASI MASYARAKAT - MIFTAKH NURHUDA MAULANA (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2019)
ABSTRACT URBAN TOURISM DEVELOPMENT BASED ON COMMUNITY PARTICIPATION IN KAMPUNG LAWAS MASPATI, SURABAYA Name :Miftakh Nurhuda Maulana Registered Number:15010034023 Study Program :S-1 Departement :Non-Formal Education Faculty :Faculty of Education Institution :State University Of Surabaya Advisor :Dr. Suhanadji, M.Si Urban tourism development based on community participation is motivated by alternative government efforts to improve the economy of local communities. This study aims to describe and analyze the forms of community participation, urban tourism development models and the factors that influence community participation in Lawas Maspati Village, Surabaya.The approach in this research uses a descriptive qualitative approach. The place of research was conducted in Lawas Maspati Village, Bubutan Sub-District, Surabaya. Data collected by interview techniques, observation and documentation. Data analysis techniques include data collection, data reduction, data display, and data verification. While the validity criteria for the data uses the source triangulation technique.The results of this research show that the form of participation given by the community in tourism development in Lawas Maspati Village has 5 ideas, funds, labor, skills and social participation. Factors affecting the residents of Lawas Maspati Village tend to participate, more visible in several factors, namely gender, age and length of stay. While the tourism development model in Lawas Maspati Village is community-based, bottom-up, and community approach, which can benefit local communities and visitors. Keywords: Community participation, Tourism development, Urban tourism ABSTRAK PENGEMBANGAN WISATA PERKOTAAN BERBASIS PARTISIPASI MASYARAKAT DI KAMPUNG LAWAS MASPATI, SURABAYA Nama :Miftakh Nurhuda Maulana NIM :15010034023 Program Studi :S-1 Jurusan :Pendidikan Luar Sekolah Fakultas :Fakultas Ilmu Pendidikan Nama Lembaga :Universitas Negeri Surabaya Pembimbing :Dr. Suhanadji, M.Si Pengembangan wisata perkotaan berbasis partisipasi masyarakat di latar belakangi oleh upaya alternatif pemerintah guna meningkatkan perekonomian masyarakat lokal. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis tentang bentuk partisipasi masyarakat dan model pengembangan wisata perkotaan di Kampung Lawas Maspati Surabaya. Pendekatan dalam penelitian ini menggunakan pendekatan kualitatif deskriptif. Tempat penelitian dilaksanakan di Kampung Lawas Maspati, Kelurahan bubutan, Surabaya. Data yang dikumpulkan dengan teknik wawancara, observasi dan dokumentasi. Teknik analisis data meliputi koleksi data, reduksi data, display data, dan verifikasi data. Sedangkan kriteria keabsahan data menggunakan teknik triangulasi sumber. Hasil penelitian menunjukkan bahwa bentuk partisipasi yang diberikan masyarakat dalam pengembangan wisata di Kampung Lawas Maspati ada 5 yaitu buah pikiran, dana, tenaga, keterampilan dan partisipasi sosial. faktor yang mempengaruhi warga Kampung Lawas Maspati cenderung berpartisipasi lebih terlihat pada beberapa faktor yaitu jenis kelamin, usia dan lamanya tinggal. Sedangkan model pengembangan wisata di Kampung Lawas Maspati berbasis masyarakat, bersifat bottom up, dan community approach.